Shear Stress Accumulation Enhances von Willebrand Factor-Induced Platelet P-Selectin Translocation in a PI3K/Akt Pathway-Dependent Manner - Fang, Jinhua; Sun, Xiaoxi; Liu, Silu; Yang, Pu; Lin, Jiangguo; Feng, Jingjing; Cruz, Miguel A.; Dong, Jing-fei; Fang, Ying; Wu, Jianhua (Frontiers in Cell and Developmental Biology, 2021)
Platelet adhesion and activation through interaction of von Willebrand factor (VWF) with platelet glycoprotein (GP) Ibα are the early key events in hemostasis and thrombosis especially under high blood shear stress. P-selectin translocation from granule to the cell surface is a typical platelet function phenotype, which makes the platelet-induced inflammatory response of flowing leukocytes possible, and can be induced by either chemical agonists (thrombin, ADP, etc.) or high blood shear stress. But, regulations of VWF mutation and blood shear stress on VWF-induced P-selectin translocation remain unclear. With flow cytometry, parallel plate flow chamber, and immunofluorescence staining techniques, we examined P-selection translocation of platelets on immobilized wild-type (WT) VWF-A1 domain and its two mutants, the gain-of-function (GOF) mutant R1308L and the loss-of-function (LOF) mutant G1324S, respectively. The results showed that the VWF-A1-induced platelet P-selectin translocation was triggered, accelerated and enhanced by fluid shear stress, and could be correlated with shear stress accumulation (SSA, the product of fluid shear stress and mechanical stimulus time); and PI3K/Akt axis was involved in the platelet P-selectin translocation. The force-triggered P-selectin translocation occurred quickly on partial platelet surface first and then extended gradually to the whole platelet surface as SSA increased. The P-selectin translocation process would be promoted by the GOF mutation (R1308L) but slowed down by the LOF mutation (G1324S). These findings demonstrated a force-enhanced regulation mechanism for the VWF-induced platelet P-selectin translocation through PI3K/Akt pathway and provided a novel insight into the mechano-chemical regulation mechanism for the key events, such as platelet activation and functional phenotype change in hemostasis and thrombosis.